Effective association between audit committees and the internal audit function and its impact on financial reporting quality: Empirical evidence from Omani listed firms. Issue 2 (14th March 2018) - Gebrayel, Elias; Jarrar, Hajer; Salloum, Charbel; Lefebvre, Quentin
Abstract : The role of the audit committee in oversight of the internal control and internal audit function has grown in the last decades as corporate governance mechanisms after the dramatic scandals and failures. This paper examines the impact of the audit committee and the presence of internal audit function on a company's financial reporting quality. Moreover, this study focus on the association between the audit committee and internal audit function and company's financial reporting quality measured as accruals quality and absolute discretionary accruals. It is hypothesized that the financial reporting quality is related to the strength of internal corporate governance mechanisms, including audit committee and internal audit and its association. Different mechanisms are being examined: audit committee size and independence, frequency of meeting, financial literacy, existence of internal audit function and its meeting independently. To test our hypothesis, we employ panel data analysis for 71 nonfinancial firms through 139 observations listed on the Muscat Securities Market during the period of 2013 and 2014. The data used in the analysis were collected from the companies' annual reports published by the Muscat Securities Market. Ordinary least squares is used to regress financial reporting quality linear variables on audit committee and internal audit. The findings suggest that audit committee meetings frequency and the presence of internal audit function positively affect a company's financial reporting quality. Hence, an audit committee that meets more frequently provides effective monitoring of financial reporting and increases the likelihood of discussing and following up any problems and findings in the financial statements and audit reports. Thus, frequent audit committee meetings provide better oversight of the annual accounts. Likewise, the internal audit function is considered an important corporate governance mechanism to safeguard the quality of financial reporting by monitoring organizational risks, assessing internal controls and detecting possible manipulation because the internal auditor evaluates financial procedures. However, results suggest that the relationship between other corporate governance mechanisms and financial reporting quality is not significant.